Design of an all-optical quaternary encoder to code decimal numbers by utilizing optical Kerr nonlinear material - Apurba Guchhait; Nirmalya Pahari; Nabin Baran Manik (Discover Electronics)
Abstract Optics and photonics offer significant advancements in the rapidly evolving fields of data processing and communication owing to their inherent parallel-processing capabilities. This paper presents a novel all-optical quaternary encoder that efficiently encodes decimal numbers by leveraging the nonlinear switching properties of Kerr-type optical materials. The proposed encoder operates entirely within the optical domain and offers multiple benefits. First, it achieves exceptionally high processing speeds owing to its optical nature. Secondly, it supports the simultaneous encoding of ( $${4}^{n}-1$$ 4 n - 1 ) different input signals expressed in ‘n’ bit quaternary states, enhancing parallel data handling. Third, unlike conventional electronic encoders that depend on electronic OR gates, this scheme eliminates the need for both electronic and optical gates, making it a versatile solution for optical communication, all-optical computation, and various photonic-device applications. The proposed approach underscores the potential for advancing optical technologies and expanding their applicability across diverse fields.